Transforming Healthcare Through Effective Health Administration Practices: A Systematic Review - almalki, Saeed safran; Alhomiany, Abdulaziz Mohammed; Alsharif, Mutlaq Zaid; ALsolumany , Faisal Jameel Ali; Alnajjar , Majdi Mohammed abed; Alsharif, Mohammed Nasser Mohammed; Al-Talhi, Sultan Olaywi; Alosaimi , Saud Mihmas Odays; Albaqami, Saad Mohammed Khalid; Alsulaimani, Mohammed Abdullah Abed; Nasraldeen, Rami Abdullah (Journal of Ecohumanism, 2024)
The role of effective health administration practices is crucial in transforming healthcare organizations by enhancing efficiency, improving patient outcomes, and promoting operational sustainability. This systematic review synthesizes the current body of knowledge on health administration practices that have demonstrated transformative impacts within healthcare settings. A comprehensive literature search across major databases, including PubMed, Scopus, and Google Scholar, was conducted, focusing on studies published in recent years. Key themes emerging from the review include workforce management, patient-centered care, digital health solutions, quality improvement methods, and financial management strategies. Findings suggest that effective health administration practices contribute significantly to optimizing healthcare delivery, reducing costs, and increasing patient satisfaction. However, challenges such as staff resistance and high implementation costs remain barriers to adopting these practices widely. This review highlights the need for continued research into long-term impacts, cost-effectiveness, and adaptability of these practices in diverse healthcare environments. The findings provide valuable insights for healthcare administrators and policymakers aiming to implement evidence-based strategies to foster continuous improvement and adaptability within healthcare systems.